A influência da fadiga nos músculos eversores durante a entorse lateral do tornozelo - Rodrigues, Karina Aparecida [UNESP] (2016)
The inversion and plantar flexion ankle sprain is one of the most common injuries that occur in daily life activities and sports. Although acute symptoms can be resolved quickly, many people report persistent pain and instability. This type of injury often occurs in the final phase of a training or competition, and even though the sprain is multifactorial, such particularity provides the establishment of a relationship between the event sprain and fatigue. In this view, the present study aims to analyze the latency and activation intensity of the brevis and longus peroneus muscles in conditions of fatigue and also compare individuals with stability and instability of the ankle. For this purpose it was initially developed a simulated platform sprains in inversion and plantar flexion, in which both feet of the volunteers were fixed and below where rested his feet were coupled force transducers, one on each side. The study included 23 female volunteers, physically active, separated into two groups: 11 were part of the group stability, had no injury history in the joint complex of the ankle in the last 12 months and another 12 in functional instability group, classified by Cumberland Questionnaire Ankle Instability Tool. To induce fatigue, it was initially recorded a Contraction Isometric Maximal Voluntary (MVIC) in eversion and plantar flexion. During the induction, the participants were instructed to maintain 70% of the MVIC. At the time the force applied was below 60% of the MVIC the protocol was interrupted and the volunteers placed in standing position on the simulator platform. Before and after fatigue were held ten simulations sprain bilaterally randomly and simultaneously to record the electromyographic signal. Thus, it was observed that after the fatigue did not change the latency, but there was a reduction of muscle contraction level, evidenced by the reduction in amplitude of the electromyographic signal. Still, there were no noticeable differences between the groups stability and instability and there was a higher activity of the peroneus brevis compared to longus. Therefore, it was concluded that the local neuromuscular control was compromised in fatigue situations, due to reduced activity level of the peroneus longus and brevis muscles. Moreover, it was not possible to observe difference in muscle behavior between stable and unstable functionally ankles.